Concpetion of Masculinity as Male Domination and Methodological Proposal to Address it (Revista Rupturas, 2020)
Since the 1990s, research on masculinity has intensified, and actions aimed at shaping and addressing the issue have been intensified. This article aims to position a novel way of conceiving, studying and addressing masculinity: as a form of structured social domination, which articulates a set of social provisions that men assume to integrate functionally into society and reproduce a particular social order. This approach has been studied empirically since 2012 and the opportunity has been taken to translate the theoretical proposal into an intervention methodology, using psychosocial supervision as a reference. The methodology has been validated in workshops and meetings with men, and the final part of the article is presented.
Keywords: masculinity; domination; disposition; supervision; gender for men